Fabrication of Papillary Composite Microstructured Aluminum Surfaces by Laser Shock Imprinting and Ablation - Zongbao Shen; Qizhi Xu; Yansong Yu; Dong Liu; Jie Ji (Metals)
Laser shock ablation is incorporated into laser shock imprinting for the fabrication of papillary composite microstructures on aluminum surfaces. The primary papillary structures are fabricated using laser shock imprinting. Subsequently, secondary structures were fabricated on the surface of these primary structures using laser shock ablation, forming composite papillary microstructures. The influence of various laser shock ablation process parameters on the formation effect of these papillary composite microstructure surfaces was investigated. The results indicate that both laser shock energy and shock frequency affect the integrity of the secondary microstructure coverage on the material surface, the height of the composite microstructure, and the surface morphology. Through comparative optimization, the optimal process parameters were determined to be 675 mJ of energy and one shock ablation. Additionally, the differences in the flow behavior of metallic materials between the center and the periphery of the beam spot, caused by the shock wave, were analyzed. The wettability of the composite microstructure aluminum surface was also explored. The variation mechanism of wettability was explained by detecting changes in the contact angle on the aluminum surface at different time intervals and analyzing changes in surface chemical composition before and after aging. Specifically, after laser shock ablation, the aluminum surface contains a large number of polar groups, making it hydrophilic. During aging treatment, these polar groups continuously adsorb non-polar alkyl organic compounds, eventually leading to hydrophobicity, with a stabilized average surface contact angle of 143°. Fluorination treatment can further achieve superhydrophobicity, with a contact angle of 151° achieved shortly after processing the composite microstructure aluminum surface.